The Rise of the American Corporate Security State : Six Reasons to Be Afraid. - Edwards, Beatrice (Berrett-Koehler Publishers, 2014)
Take Back Our Civil Liberties!Beatrice Edwards, executive director of the organization representing Edward Snowden and four other NSA whistleblowers, argues that we now live in a Corporate Security State, where the government is more interested in protecting the companies that serve it than the citizens who support it. Hheavy domestic surveillance, political persecution of dissenters, the threat of indefinite detention codified into law-how did we get here? And is there a way out?Edwards details how intelligence agencies took advantage of 9/11 to illegitimately extend the government's reach. C.